(3GdJPgjH aj TQM GdJgPjHs - (3GdTGgQhOj, GdHSWGej, eMeO Hf TQas ((3jhSa GdMdHj GdCRgQj GdTGaYjs)
(3ChdgG (B:s
(3CMeOc jG ef CfWb efWb YHOg HBjGJ LdGdg(B... (3hHYO ajbhd(B... (3eMeO Hf TQa(B... (3deG cGf Yde GdefWb(B...s
(3BNQgG (B:s
(3Ydi eG PcQ ef MOhO GdehVhYGJ hZjQgG cPdc jbGd (B... (3gPG BNQ eG GQOfG EjQGOg aj gPG GdcJGH hGddg CYde HGdUhGHs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc(B: (3Ydj eMeO QVG gGOj cGTa GdZWGAs
Keywords: (3GdadSaI hGdefWbs